2012
DOI: 10.1111/j.1600-051x.2012.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of alveolar bone following implantation of an rhGDF‐5/PLGA composite into 1‐wall intra‐bony defects in dogs: 24‐week histometric observations

Abstract: The rhGDF-5/PLGA appears to support alveolar bone healing/regeneration and the rhGDF-5/PLGA high dose uniquely increased maturation of the regenerated bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…These materials may be customized with respect to porosity, interconnectivity, compressive strength, and degradation. Some previously tested synthetic graft materials for bone regeneration are biphasic calcium phosphate (Cordaro et al 2008;Frenken et al 2010), porous titanium (Delgado-Ruiz et al 2014;Lyngstadaas et al 2015), hydroxyapatite (Crespi et al 2012), tricalcium phosphate (Horowitz et al 2009;Shalash et al 2013) and polymers (Bertoldi et al 2008;Park et al 2012).…”
mentioning
confidence: 99%
“…These materials may be customized with respect to porosity, interconnectivity, compressive strength, and degradation. Some previously tested synthetic graft materials for bone regeneration are biphasic calcium phosphate (Cordaro et al 2008;Frenken et al 2010), porous titanium (Delgado-Ruiz et al 2014;Lyngstadaas et al 2015), hydroxyapatite (Crespi et al 2012), tricalcium phosphate (Horowitz et al 2009;Shalash et al 2013) and polymers (Bertoldi et al 2008;Park et al 2012).…”
mentioning
confidence: 99%
“…When absorbable collagen sponge was compared to β‐TCP, the latter carrier induced significantly more bone formation, probably due to slower release of the growth factor . The positive effect of GDF‐5 on alveolar bone appears to continue long‐term .…”
Section: Growth and Differentiation Factor‐5 In Periodontal Regenerationmentioning
confidence: 99%
“…Currently, numerous species, including nonhuman primates, dogs, rodents, sheep, miniature pigs, rabbits, hamsters, ferrets and other animals, have been used to evaluate the pathogenesis and treatment of periodontitis . However, there is no simple and reproducible animal model that adequately replicates the pathogenesis of periodontal disease in the way it occurs in humans; furthermore, the models described are not always free from bias and consequently this interferes with the interpretation of the results .…”
Section: Preclinical Models Used In Periodontal Researchmentioning
confidence: 99%
“…However, placing a notch at the alveolar bone crest level to mark the apical limit of instrumentation may result in overestimation of the pathological process . The stimulating effect of the notch itself to induce cementum formation has also been discussed . It has been reported that intrabony defects of one, two and three walls often display spontaneous bone healing, and surgical defects treated without any regenerative modality sometimes demonstrate a certain amount of bone regeneration at the base of the defect .…”
Section: Defect Models Replicate Periodontal Pocket/diseasementioning
confidence: 99%
See 1 more Smart Citation